Shear strength of municipal solid waste rejected from material recovery facilities in the city of São Paulo, Brazil - Juarez, Mariana Barbosa [UNESP]; Mondelli, Giulliana [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Associação Brasileira de Mecânica dos Solos, 2023)
The mechanical behavior of municipal solid waste (MSW) is a critical issue in environmental geotechnics, given the pollution and public health risks associated with slope failures. In Brazil, waste composition is expected to change due to the hierarchy of sustainable practices established by the National Solid Waste Policy, which aims to improve the recovery of organic and recyclable materials. Not much progress has been made since the implementation of this law; thus, its effects on the design and operation of landfills are not fully clear. This study presents and discusses compaction and shear strength parameters of dry MSW after mechanical sorting of medium and large recyclable items and shredding. The maximum dry unit weight for the standard Proctor compaction test ranged from 6.6 to 10.0 kN/m3 and the optimum moisture content ranged from 20% to 42%. Stress-displacement curves of direct shear tests showed strain hardening and shear strength parameters of Mohr-Coulomb envelopes were displacement-dependent. The friction angle ranged from 3.2° to 42.9° and the cohesion intercept ranged from 1.3 to 31.3 kPa, at a displacement of 9 mm (15% of the specimen length). These results are in line with the literature, since a high content of waste materials that proved to affect geotechnical properties, such as plastic, paper, cardboard, textile, and glass, remained after pre-treatment.
Keywords: Municipal solid waste; Sorting; Shredding; Compaction; Friction angle; Cohesion